Simulation of the Ni3Al intermetallic inclusion growth process during direct laser deposition using Ni-based superalloy powder - Alekseev, Andrey V.; Turichin, Gleb A.; Klimova-Korsmik, Olga G.; Valdaytseva, Ekaterina A.; Rashkovets, Mariia V.; Nikulina, Aelita A. (Materials today : proceedings, 2020)
The mechanical properties of Ni-based superalloys are based on the hardening γ′-phase which is mainly Ni3Al intermetallic compound with an ordered structure (Ll2). A mathematical model of γ′-phase inclusions growth during direct laser deposition was developed to predict parameters of the hardening phase. The subject of the study is the assessment of the applicability of the model as well as its adjustment if it is necessary. A series of experiments on growing thin walls were carried out to confirm the operability of this model. The power of the laser source was changed (450, 600, 900 and 1200 W) at constant values of the processing speed (1.2 mm/s), powder feed rate (45 g/min) and the beam diameter in the processing region (1.2 mm) in these experiments. The average size of γ′-phase inclusions was determined by means of a metallographic study and amounted to 10.74, 15.19, 25.62 and 24.49 nm, respectively. A comparison of the calculated and experimental values of the inclusions size showed that the proposed model gives satisfactory results in a limited range of cooling rates. Probably, it is connected with the fact that the growth of grains due to formation of a new phase stops due to a decrease of the concentration of components involved in the chemical reaction in the adjacent zone and the growth due to the absorption of neighboring grains does not have enough time to occur.